THE EMPIRICAL IDENTITY OF MORAL JUDGEMENT. - KUMAR, VICTOR (Philosophical Quarterly, 2016)
I argue that moral judgement is a natural kind on the grounds that it plays a causal/explanatory role in psychological generalizations. I then develop an empirically grounded theory of its identity as a natural kind. I argue that moral judgement is a hybrid state of moral belief and moral emotion. This hybrid theory supports the role of moral judgement in explanations of reasoning and action and also supports its role in a dual process model of moral cognition. Although it is composed of moral belief and moral emotion, moral judgement is unified, like other natural kinds, in virtue of underlying mechanisms that generate homeostasis among its components. Finally, this theory about the unity of moral judgement resolves a longstanding puzzle about moral motivation. The view explains how it is that moral judgements motivate all on their own but not all the time.